Investigating the synergy of fast co-pyrolysis of spent coffee ground and disposed urban facemask: analysis of kinetics and product compositions - Idris, Imad A.; Nisamaneenate, Jurarat; Atong, Duangduen; Kaewpengkrow, Prangtip Rittichote; Sricharoenchaikul, Viboon (My University, 2025)
This study investigates the thermo-kinetic behavior and product distribution during the co-pyrolysis of spent coffee grounds (SCG) and facemasks (FM). TGA was employed to evaluate the kinetics and thermodynamics of the pyrolysis process by segmenting the thermal decomposition into stage I (200 – 360 °C) and stage II (360 – 550 °C), while Py-GC/MS was used to analyse the product composition. SCG and FM blends with varying ratios by wt.% (SCG:FM = 100:0, 75:25, 50:50, 25:100, and 0:100) were subjected to pyrolysis at four heating rates (5, 10, and 30 °C/min). The decomposition curves were deconvoluted using Fraser-Suzuki deconvolution method into four peaks related to biomass pseudo-components and FM degradation. The deconvoluted curves showed potential synergistic interaction at the lignin and FM decomposition zone (460 – 500 °C). The kinetic analyses were carried out using three model-free methods to investigate the activation energy (Ea) and thermodynamics of co-pyrolysis. The lowest Ea value was obtained at SCG25 %FM%75 % (305.1 – 239 kJ/mol), mostly pronounced in stage II. Py-GC/MS analysis of the co-pyrolysis products demonstrates that the decomposition of polypropylene polymer of the FM promoted the formation of aliphatic hydrocarbons and reduces the overall acidity. This effect was further amplified at higher pyrolysis temperatures (450 – 650 °C). The blending ratio also plays a significant role, with a higher polymer content (SCG25 %FM75 %) leading to a more aliphatic products and a significant decline in carboxylic acids and anhydro-sugars. Moreover, co-pyrolysis reduced the N containing compounds significantly. Finally, policy implications and recommendations for co-pyrolysis adoption were incorporated. Overall, this study highlights the potential of utilizing waste material like SCG and FM for the sustainable production of valuable chemicals and fuels.
Keywords: Co-pyrolysis; Facemask; Py-GC/MS; Spent coffee ground; Synergistic effect